Gendarmerie Units in the Territory of the Morava Banovina (1929–1941) - Velojić, Dalibor Z. (Collection of Papers of the Faculty of Philosophy in Priština, 2025)
This paper examines the formation, structure, and functioning of gendarmerie units in the territory of the Morava Banovina, within the Kingdom of Yugoslavia, during the interwar period. It highlights the main issues faced by this military police force, which played a significant role in maintaining order and peace, as well as suppressing communist propaganda. The paper is based on archival materials and relevant literature.